The Relationship Between Religiosity and Altruistic Behavior on Covid-19 Volunteers of Muhammadiyah Sidoarjo: Hubungan Antara Religiusitas dengan Perilaku Altruistik pada Relawan Covid-19 Muhammadiyah Sidoarjo - Rubiantari, Mulyani; Hazim, Hazim (Journal of Islamic and Muhammadiyah Studies, 2023)
This Reaserch is motivated by the phenomenom of Covid-19 volunteers who expeinece altruistic behavior problems. This reaserch doing to know the positive relationship between religiosity and altruistic behavior in Covid-19 Muhammadiyah Sidoarjo volunteers. The hypothesis proposed by the researcher is that there is a positive relationship between religiosity and altruistic behavior in Covid-19 Muhammadiyah Sidoarjo volunteers. the quantitative method was chosen by researcher to achieve the objectives of this study. Responden in this study were taken based on Isaac and Michael’s scale table with 5% of the population 226 taken into 139 research subjects. This study used an altruistic behavior scale and religiosity scale. The results of the product moment analysis showed that the rxy correlation coefficient was 0,268 with a significance of 0,001 (P< 0,05) meaning that there was a significance positive relationship between altruistic behavior and religiosity in Covid-19 volunteers of Muhammadiyah Sidoarjo. The effective Contribution of religiosity was 6,5 % towards altruistic behavior. that there are 93,5 % of other factor that influence outside the religiosity variable.